Diamante dopado com boro como um possível suporte de eletrocatalisador de PEMFC - Mattoso, Samuel Henrique (Universidade Federal de São Carlos, 2020)
Proton-exchange membrane fuel cells (PEMFCs) are promising candidates for the green conversion of hydrogen into electric energy. A considerable problem pre-venting the large-scale applications of PEMFCs is the inadequate durability of the supported electrocatalyst layer. Carbon blacks (CBs) such as Vulcan XC-72 are commonly used as the carbon support, however its stability is limiting for long term PEMFC use. CB in the cathode is oxidized in the PEMFC start and stop cycles, detaching the Pt nanoparticles and promoting their agglomeration, which leads to performance loss. This degradation is due to the high potentials caused by fuel starvation and to the accelerated corrosion rate induced by the Pt catalysts. Boron-doped diamond (BDD) has interesting properties, such as high chemical and thermal stability, that make it desirable as a PEMFC electrocatalyst support material. The most widespread method for producing BDD is chemical vapor dep-osition (CVD), since it is efficient in dopant control and makes diamond with consistent characteristics. The physicochemical and electrical properties of BDD are affected by the amount of non-diamond carbon (NDC) present in the diamond matrix, by the grain size and by the boron doping. All of this in turn are controlled by the CVD conditions that are employed, such as source gas mixture ratios and deposition pressure/power. BDD can be synthesized as a film or a powder; the latter is most wanted for energy applications as it has a higher surface area. BDD particles can be synthesized by a core-shell approach, in which a powder sub-strate, such as nanodiamond or glassy carbon, is coated with a layer of BDD. The BDD overlayer can be observed with scanning electron microscopy (SEM), which allows the assessment of the particles’ morphology. Raman spectroscopy is widely used for evaluation of the BDD microstructure, as BDD materials have a wide range of Raman spectra that correlate with the amount of NDC, grain size and defect density. SEM and Raman spectroscopy enable the distinction of sp2 and sp3 bonded carbon domains, which allows the correlation of the BDD mate- 6 rials’ microstructure with the observed electrochemical properties. These proper-ties can be evaluated by cyclic voltammetry, in which redox peaks may be ob-served due to the presence of NDC. Additionally, redox probes such as [Fe(CN)6]3–/4– can be used, with the electrochemical response being sensitive to the surface or electronic properties of BDD. Anodic polarization is used to analyze the stability of the powders, as less-stable powders show more extensive oxida-tion. Finally, it is possible to attach Pt nanoparticles to BDD to test their viability as electrocatalyst support. After attachment of the Pt nanoparticles, it is possible to evaluate the performance and durability of the potential BDD supports with the previously mentioned electrochemical techniques and with accelerated long-term stability tests.
Boron-doped diamond as a possible PEMFC electrocatalyst support material
Keywords: Células a combustível de membrana trocadora de prótons; Diamante dopado com boro; Suporte de eletrocatalisador; Deposição química em fase de vapor; Carbono não diamante; Espectroscopia Raman.; Voltametria cíclica; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA